Species-Specific Responses of Baikal Amphipods to Artificial Lighting of Varying Intensity and Spectral Composition - Dmitry Karnaukhov; Yana Ermolaeva; Maria Maslennikova; Bogdan Osadchy; Sofya Biritskaya; Arina Lavnikova; Natalia Kulbachnaya; Anastasia Solodkova; Artem Guliguev; Ivan Kodatenko; Diana Rechile; Kristina Ruban; et al. (Limnological Review)
Light pollution can have a variety of effects on aquatic organisms. Despite the fact that amphipods are one of the model organisms for studying the effects of light among macroinvertebrates, data on the reaction of Baikal amphipods to artificial lighting are limited and contradictory. In this study, we examine the response of Baikal littoral and sublittoral amphipod species to artificial lighting of varying intensity and spectral composition. In the experiments, amphipods were exposed to warm and white light at three different intensity ranges (5–15, 20–35, and 80–100 lx), as well as blue and red light. As a result, it was found that the reaction of Baikal amphipods to different lighting conditions was species-specific and dependent on the spectral composition of the light more so than the intensity of the light. In particular, white LED light generally repulsed E. cyaneus, but tended to attract A. godlevskii. P. cancelloides, and G. fasciatus, suggesting that white LED light may have a greater negative impact on wildlife than warm LED light. Generally, artificial light influences the behavior of Baikal amphipods, and an increase in light pollution on Lake Baikal may lead to changes in the littoral community in certain areas of the lake subject to pollution.